Pengembangan Video Youtube dan Google Sites Sebagai Media Pembelajaran Interaktif Pada Materi Tata Nama Senyawa Anorganik di SMA Negeri 30 Jakarta - Sulistyowati Nur Astuti; Syaadah, Rika Siti; Paristiowati, Maria (LPPM Universitas Negeri Jakarta, 2024)
This research aims to develop learning videos and learning websites as interactive learning media on the nomenclature of inorganic compounds. Learning videos are uploaded on the YouTube platform and learning websites are uploaded via the Google sites platform. The research subjects were 103 students in classes X-1, X-2 and X-8 at SMA Negeri 30 Jakarta. This research was carried out based on the role of digital media in supporting understanding of the nomenclature of inorganic compounds. Based on the analysis of students' needs, it is necessary to create digital media that can help deepen students' understanding of material accessed via devices or gadgets. The research method used is the Research and Development (R&D) method. Based on the results of learning media trials, an average percentage of media practicality was obtained at 82.3% in the very good category. At the validation stage by the tutor, its validity was tested using Aiken's V of 0.93 which indicated the high category.